2018
DOI: 10.1177/0269881118772449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of paliperidone palmitate one-month formulation on relapse prevention in patients with schizophrenia: A post-hoc analysis of a one-year, open-label study stratified by medication adherence

Abstract: Background:Limited data are available to help identify patients with schizophrenia who are most likely to benefit from long-acting injectable antipsychotics.Aim:To investigate the efficacy of long-acting injectable antipsychotic paliperidone palmitate one-month formulation for preventing relapses, factors influencing time to first relapse, and the effect of different antipsychotic adherence levels on time to first relapse in Chinese patients with schizophrenia.Methods:This was a post-hoc analysis from an open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The most frequent reason to start OAP was the first antipsychotic treatment, while PP1M was initiated in the case of lack of adherence, lack of efficacy of previous treatments, or concomitant lack of adherence and efficacy, which is to be expected due to the therapeutic indication of PP1M. Again, the current results corroborate previous research ( 20 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The most frequent reason to start OAP was the first antipsychotic treatment, while PP1M was initiated in the case of lack of adherence, lack of efficacy of previous treatments, or concomitant lack of adherence and efficacy, which is to be expected due to the therapeutic indication of PP1M. Again, the current results corroborate previous research ( 20 ).…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have shown that PP1M provides good outcomes in relapse prevention and hospitalizations. This is even more significant in patients with prior history of non-adherence to treatment, which is also highlighted by the reduction in bed use in fully compliant patients under PP1M (20,21). LAIs have shown better outcomes in a real-world setting-namely in hospitalizations and relapse risk-compared to OAPs (22), with lower rates of treatment failure.…”
Section: Introductionmentioning
confidence: 98%
“…[14][15][16][17][18][19] Poor adherence to antipsychotic treatment is a significant risk factor for relapse in Chinese patients. 20 However, to date, these data were obtained in clinical trial participants, and to our knowledge, no real-world database studies have compared treatment patterns between PP1M and oral SGAs among Chinese or Japanese patients with schizophrenia. Therefore, we conducted a large, retrospective real-world cohort study in patients with schizophrenia in China and Japan to compare persistence and adherence between PP1M and oral SGAs.…”
mentioning
confidence: 99%
“…4,12 This target population may also derive the greatest incremental benefit from a treatment switch to PP1M. 4,12,39,41 17,19,42 Probability of adherence was consistent across all cycles unless a patient switched from PP1M to an OAA or from an OAA to a different OAA, and probability of relapse was consistent across all cycles and treatment unless a patient's adherence status changed. At each cycle, patients were subject to nonadherence or adherence, regardless of their adherence status in the previous cycle.…”
Section: Model Inputsmentioning
confidence: 99%